The Fourier-Laplace Transform—A Conjugate Link Between the Material Brain and the Conscious Mind - Brändas, Erkki J. (Frontiers in Human Neuroscience, 2021)
Recent attempts to establish the quantum boundaries of life is pursued. A pre-existing view of quantum biology is supplemented by the formulation of modern advances in theoretical chemical physics and quantum chemistry. The extension to open system dynamics entails a self-referential amplification supporting the signature of life as well as consciousness via long-range correlative information, ODLCI. The associated negentropic coherence permeates hierarchical and functional organization at multiple levels. In this communication we will derive and review one of the most important mathematical tools, i.e., the combined use of the Fourier- and the Laplace transform. It is shown that an underlying operator algebra facilitates the formulation of the conjugate relationship between energy-time and momentum-space. Implications from augmented general dilation analytic operator families provide novel information-based representations and yield, inter alia, a thermo-qubit syntax for communication, which are required to support the quantum Darwinian view of life.